A head‐to‐head comparison between Guardian Connect and FreeStyle Libre systems and an evaluation of user acceptability of sensors in patients with type 1 diabetes. Issue 7 (5th July 2022) - Yeoh, Ester; Png, Doanna; Khoo, Jonathon; Chee, Ying Jie; Sharda, Puja; Low, Serena; Lim, Su Chi; Subramaniam, Tavintharan
Abstract: Aims: A user‐calibrated real‐time continuous glucose monitoring (rt‐CGM) system is compared to a factory‐calibrated flash glucose monitoring (FGM) system and assessed in terms of accuracy and acceptability in patients with type 1 diabetes (T1D). Methods: Ten participants with T1D were enroled from a specialist diabetes centre in Singapore and provided with the Guardian Connect with Enlite Sensor (Medtronic, Northridge, CA, USA) and first‐generation Freestyle Libre System (Abbott Diabetes Care, Witney, UK), worn simultaneously. Participants had to check capillary blood glucose four times per day. At the end of week 1 and week 2, participants returned for data download and were given a user evaluation survey. Results: Accuracy evaluation between Guardian Connect and Freestyle Libre includes the overall mean absolute relative difference value (9.7 ± 11.0% vs. 17.5 ± 10.9%), Clarke Error Grid zones A  +  B (98.6% vs. 98.1%), sensitivity (78.9% vs. 63.4%), and specificity (93.4% vs. 81.0%). Notably, time below range (<3.9 mmol/L) was 10.5% for FGM versus 2% for rt‐CGM. From the evaluation survey, 90% of participants perceived rt‐CGM to be accurate versus 40% for FGM, although the majority found both devices to be easy to use, educational, and useful in improving glycaemic control. However, due to the cost of sensors, only 30% were keen to use either device for continuous monitoring. Conclusions: Although rt‐CGM was superior to FGM in terms of accuracy, the value of glucose trends in both devices is still useful in diabetes self‐management. Patients and clinicians may consider either technology depending on their requirements.